Hegel's conception of the determinate negation - Sparby, Terje Stefan. (Critical Studies in German Idealism, 2015)
"The determinate negation" has by Robert Brandom been called Hegel's most fundamental conceptual tool. In this book, Terje Sparby agrees about the importance of the term, but rejects Brandom's interpretation of it. Hegel's actual use of the term may at first seem to be inconsistent, something that is reflected in the scholarship. However, on closer inspection, three forms of determinate negations can be discerned in Hegel's texts: A nothing that is something , a moment of transformation through loss (like the Phoenix rising from the ashes), and a unity of opposites . Through an in-depth interpretation of Hegel's work, a comprehensive account of the determinate negation is developed in which these philosophically challenging ideas are seen as parts of one overarching process.